Changes in the Position of Ice Edge in North Caspium and the Prospects of Their Forecasting (Ob Izmenchivosti Polozheniya Kromki lda v Severnom Kaspii Vozmozhnosti ee Predskazaniya) - Karakash,E. S. (1971)
Yearly, monthly and ten-day changes in the position of ice edge in the North Caspium are discussed in detail, giving data on the width of shore ice and drift ice belts. The ice edge is related to the intensity of atmospheric circulation, air temperature, iciness and synoptic processes prior to forecasting. Equations used in forecasting the position of ice edge have large correlation coefficients (more than 80). The reliability of forecasting based on equations exceeds the natural reliability and is slightly smaller than the inertial reliability, no matter what the calculation errors are. The data on iciness in the North Caspium are reduced to the 15th day of each month from 1928 to 1962. In addition, coordinates of ice edge are given for the period. (Author) Trans. of Gosudarstvennyi Okeanograficheskii Institut. Trudy (USSR) v76 p80-103 1964, by M. Slessers.